(untitled) (International Journal of Physiotherapy, 2015)
Background: Motor control exercises are isolated strengthening exercise for the deep spinal muscles (transverse abdominus, multifidus) whereas Core stability is achieved by global strengthening of the core muscles. There are not much studies available in the literature done or studied the short term effect of the motor control and core stabilization on subjects with low back pain. Therefore, the purpose of this study to find the comparative effect of motor control exercises versus core stabilization exercises on improvement of pain and disability in subjects with mechanical low back pain. Method: An experimental study design, 30 subjects with non-specific mechanical low back pain were randomized into 2 groups with 15 subjects each in Group A and Group B. Subjects in Group A received Motor control exercises and subjects in Group B received Core stability exercises. Both the group received conventional exercises. The duration of intervention was given for two weeks. Outcome measurements such as pain using VAS, Functional disability using Oswestry Disability Index Questionnaire were measured before and after two weeks of intervention. Results: Analysis using paired ‘t’ test and wilcoxon signed rank test found that there is a statistically significant improvement (p<0.05) in pain, functional disability within the groups. Comparative analysis using independent ‘t’ test and Mann Whitney U test for comparison of difference in improvement in VAS and ODI between two groups, it was found that there was significant difference in improvement of VAS and ODI between groups. Group-A showed better improvement in VAS and ODI compared to Group B with an effect size of 1.47 and 0.99 respectively. Conclusion: It is concluded that the Motor control exercises showed statistically significant improvement in reducing back pain and disability when compared to the Core Stabilization exercises. Thus, performing Motor Control exercises reduces pain and disability significantly compared to Core stabilization among non specific mechanical low back ache subjects.